Endothelial Cells Potentially Participate in the Metastasis of Triple-Negative Breast Cancer - Yanfei Ma; Yanghong Li; Pengwei Guo; Jingjie Zhao; Qiang Qin; Jiajia Wang; Zhengfang Liang; Dalong Wei; Zechen Wang; Jiajia Shen; Siyuan He; Qianli Tang; et al. (Journal of Immunology Research)
Inhibition of triple-negative breast cancer metastasis has long been a challenge, mainly due to the difficulty in identifying factors that contribute to this process. In this study, freshly isolated triple-negative breast cancer biopsied cells obtained from consenting patients were subjected to flow cytometry and bioinformatic analysis to identify three endothelial cell subclusters: EC (ATP1B3), EC (HSPA1B), and EC (KRT7) in the tumor microenvironment. These endothelial cell subclusters exhibited distinguishing biological features. Based on differentially expressed genes derived from the subclusters, gene set enrichment analysis showed that EC (ATP1B3) and EC (HSPA1B) contribute to the process of metastasis, for example, in fibrosarcoma and anaplastic carcinoma. In this study, we identified the heterogeneity of endothelial cells in the human breast cancer and have provided insights into its role in metastasis.